Promoting Healthy Aging During COVID‐19. Issue 3 (26th January 2021) - Batsis, John A.; Daniel, Kathryn; Eckstrom, Elizabeth; Goldlist, Kady; Kusz, Halina; Lane, Douglas; Loewenthal, Julia; Coll, Patrick P.; Friedman, Susan M.
Abstract : Older adults have been markedly impacted by the coronavirus disease 19 (COVID‐19) pandemic. The American Geriatrics Society previously published a White Paper on Healthy Aging in 2018 that focused on a number of domains that are core to healthy aging in older adults: health promotion, injury prevention, and managing chronic conditions; cognitive health; physical health; mental health; and social health. The potentially devastating consequences of COVID‐19 on health promotion are recognized. The purpose of this article is multifold. First, members of the Healthy Aging Special Interest Group will present the significant difficulties and obstacles faced by older adults during this unprecedented time. Second, we provide guidance to practicing geriatrics healthcare professionals overseeing the care of older adults. We provide a framework for clinical evaluation and screening related to the five aforementioned domains that uniquely impact older adults. Last, we provide strategies that could enhance healthy aging in the era of COVID‐19.